(untitled) (American Journal of Business Management, Economics and Banking, 2024)
Blockchain technology was initially linked to the rise of cryptocurrencies such as bitcoin, which was introduced in 2009. Since then, however, blockchain has evolved to become the basis for many decentralized applications (dApps). In this article, we look at how blockchain technologies have developed, what opportunities they provide today and what prospects await them in the future.